Sunflower yield in three different stages of artificial defoliation - Butignol, Cesar Assis (Pesquisa Agropecuaria Brasileira, 2014)
In a field test conducted at Florianópolis (SC), in 1981, the effect of defoliation in sunflower plants was determined. The experiment was conducted as a 3 x 4 factorial, in completely randomized blocks, being the culture stages 3.1, 4.1 and 5.1 and the defoliation levels 0; 33,3; 66,6 and 100% the factors studied. The statistical analysis of the results showed that the number of seeds were affected by the stages 3.1 and 4.1 of defoliation, staying the same number of seeds when the defoliation was done at stage 5.1; the kernel weight decreased as the defoliation level increased, in all the three stages. Estimated yield/plant at 3.1 stage was smaller than control after 60% defoliation and any level in 4.1 and 5.1. The greatest reduction was associated with the greatest defoliation level, being the stage 4.1 the most sensible to the lost of leaf area.